Interaction between a coaxial cavity and low beta intense electron beams - Keiichi Kamada; Takashi Nishiguchi; Keiichi Ishibana; Masaki Kamada; Ritoku Ando (Вопросы атомной науки и техники, 2004)
Experiments and simulations for intense relativistic electron beams with energy of <1 MeV and current of several kA that pass through a gap are carried out. A criterion is proposed for the gap length through which the beam current passes without loss, i.e. no electron is reflected by virtual cathode. The time evolutions of energy and current of an intense electron beam can be modified using a gap structure and a coaxial cavity.